Chromosomal instability and a deregulated cell cycle are intrinsic features of high‐risk gastrointestinal stromal tumours with a metastatic potential - Heidi Maria Namløs; Ksenia Khelik; Sigve Nakken; Daniel Vodák; Eivind Hovig; Ola Myklebost; Kjetil Boye; Leonardo A. Meza‐Zepeda (Molecular Oncology, 2023)
Patients with localised, high‐risk gastrointestinal stromal tumours (GIST) benefit from adjuvant imatinib treatment. Still, approximately 40% of patients relapse within 3 years after adjuvant therapy and the clinical and histopathological features currently used for risk classification cannot precisely predict poor outcomes after standard treatment. This study aimed to identify genomic and transcriptomic profiles that could be associated with disease relapse and thus a more aggressive phenotype. Using a multi‐omics approach, we analysed a cohort of primary tumours from patients with untreated, resectable high‐risk GISTs. We compared patients who developed metastatic disease within 3 years after finishing adjuvant imatinib treatment and patients without disease relapse after more than 5 years of follow‐up. Combining genomics and transcriptomics data, we identified somatic mutations and deregulated mRNA and miRNA genes intrinsic to each group. Our study shows that increased chromosomal instability (CIN), including chromothripsis and deregulated kinetochore and cell cycle signalling, separates high‐risk samples according to metastatic potential. The increased CIN seems to be an intrinsic feature for tumours that metastasise and should be further validated as a novel prognostic biomarker for high‐risk GIST.